Zilicio : generador de aplicaciones multiplataforma. parte 1 : Backend Generator (2017)
This project is focused on the development of Zilicio: an automation framework built to generate native and multiplatform mobile applications. The present document describes the process of conception and development of the BackEnd generator; a fundamental component that allows the exposure of REST web services, and the management of the content that will be consumed through the mobile applications.